2018
DOI: 10.1080/10937404.2018.1514829
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ether (PBDE) neurotoxicity: a systematic review and meta-analysis of animal evidence

Abstract: A recent systematic review (SR) and meta-analysis of human studies found an association between prenatal serum polybrominated diphenyl ethers (PBDE) concentrations and a decrease in the IQ of children. A SR of experimental developmental animal PBDE-mediated neurotoxicity studies was performed in the present study. Outcomes assessed included measures related to learning, memory, and attention, which parallel the intelli9ence-related outcomes evaluated in the human studies SR. PubMed, Embase, and Toxline were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…1B,C). These presynaptic defects and the pronounced effect of 6-OH on evoked activity under the Bic washout treatment paradigm, which has been previously Certain hydroxylated PBDEs impair neuronal MEK-ERK signaling 8 published as a model of in vitro plasticity (63), may partially explain the reported relationship between learning deficits and BDE-47/99 exposure in animal studies (9), as it is known that their hydroxylated metabolites can be produced endogenously, primarily via CYP2B6, which is dynamically expressed in the brain (31)(32)(33)(85)(86)(87).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1B,C). These presynaptic defects and the pronounced effect of 6-OH on evoked activity under the Bic washout treatment paradigm, which has been previously Certain hydroxylated PBDEs impair neuronal MEK-ERK signaling 8 published as a model of in vitro plasticity (63), may partially explain the reported relationship between learning deficits and BDE-47/99 exposure in animal studies (9), as it is known that their hydroxylated metabolites can be produced endogenously, primarily via CYP2B6, which is dynamically expressed in the brain (31)(32)(33)(85)(86)(87).…”
Section: Discussionmentioning
confidence: 79%
“…Concerningly, a substantial amount of research has established the relationship of PBDE exposure levels with behavioral deficits in humans, as well as in animal models. Recently, several large-scale and systematic reviews have concluded that PBDE exposures impact externalizing behaviors and IQ in children and that BDE-47, -99, and -209 affect learning in animal studies (6)(7)(8)(9). There is also concern for the relationship between environmental toxins like PBDEs and autism spectrum disorders (ASD), though the evidence is less conclusive, especially in human studies (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Effects in humans and laboratory animals are generally similar. Independent, systematic reviews undertaken by the US National Academy of Medicine and the International Agency for Research on Cancer confirm and validate these findings [ 214 215 ].…”
Section: Impacts Of Ocean Pollution On Human Healthmentioning
confidence: 79%
“…Our results are congruent with a disrupted developmental trajectory of the Social Processing Domain as outlined in the 2010 NIMH Research Domain Criteria (RDoC) framework 1 ; a key characteristic of ASD pathology. Our work is further strengthened by the use of the litter as the unit of statistical analysis, thus overcoming risk of bias (RoB) of individual studies 99 and inter-individual variability. Further, DE-71 produced the common hormetic response, such that only 0.1 but not 0.4 mg/kg exhibited most of the behavior changes even though there was a dose-dependent increase in brain accumulation of ∑PBDE congeners.…”
Section: Discussionmentioning
confidence: 99%